Numerical Simulation-Based Optimization of Contact Stress Distribution and Lubrication Conditions in the Straight Worm Drive - He, Y.; Li, G.F.; Zhao, Y.P.; Sun, Y.; Jiang, G.Z. (Проблемы прочности, 2018)
Tooth contact area optimization/meshing of the straight worm pair is vital for improving its operation efficiency. Geometric parameters of a worm helicoid were derived via the gear meshing theory using the equations of the instantaneous contact line. The visualization function and powerful computing capability of MATLAB are used for the numerical analysis where the instantaneous contact line distribution is simulated for particular worm drive parameters, which yields the induced curvature and slip angle in the direction of the line. The above results are used for further optimization of the meshing performance of the straight worm gear and identification of its influencing factors. A case study of the particular cylindrical worm gear in compliance with the GB 10085-1988 Standard of China demonstrate that a reasonable selection of worm gear parameters can extend the contact line and the working range of the tooth surface of the worm gear and/or make the contact line distribution along the worm wheel more uniform, thus improving the local meshing performance